Marketing strategy for spotless - Romadhona, Prabadika Hadyan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Spotless is a pioneering brand in the shoe care and hygiene category. Spotless was founded in 2015 with a vision of being a one-stop solution for all shoe hygiene and care needs. In the last six months, Spotless has experienced a significant increase in sales from July to December 2021. Spotless has experienced a 6-fold increase in sales and a 10-fold increase in marketing costs. Spotless's current goal is to maximize marketing strategies on digital platforms to introduce its products to a broader market and improve its operations that are still adjusting to current sales conditions to make it grow and stabilize existing sales. This study aims to identify marketing strategies or activities that can be used to effectuate and optimize marketing costs. These marketing strategy activities can help to increase sales and reduce marketing costs that now account for up to half of sales. This study will use qualitative research methods to observe all of Spotless's marketing activities and plan marketing strategies. The primary data for this study came from interviews with employees, consumers, and management. Secondary data for this study comes from journals, books, and articles to gain information and understanding about the theory and internal and external conditions of Spotless. Data analysis techniques in this study used internal analysis and also external analysis. This study aims to analyse the internal and external conditions of Spotless, aiming at planning and developing business and marketing strategies and providing implementation of programs that Spotless will run.